RANCANG BANGUN APLIKASI CHATTING BERBASIS WEB PADA PT SKEMANUSA CONSULTAMA TEKNIK - Muryadi, Muryadi; Zailani, Achmad Udin; Kurniawan, Yudi (Infotech: Journal of Technology Information, 2020)
Communication, discussion, and file sharing between divisions in a company is something every employee often does. The problem in this research is that not all users are connected smoothly so that it hinders communication and file transfers and in communication between divisions they have to install various applications on cellphones and PC users. This reduces the duration of time and efficiency in work. To solve this problem, a web-based chat application was designed. Because the development of these applications must use a good and structured design. Web-based chat application was created to solve this problem. This web-based application can be accessed via a web browser without having to install the application on a cellphone or laptop user. Based on the design of a web-based chat application that has been created, it is expected to be a solution for discussing, communicating and sharing files between employees in a company. In addition, it is useful to keep in touch and share files without having to install applications on cellphone or laptop users. The result of this research is that this web-based chat application can be a solution to keep communicating between employees who have difficulty accessing the internet.